Africanization of Christianity: Henry Venn’s indigenization of Christianity - Ekpenyong Obo Ekpenyong; Ibiang Obono Okoi (Center for Humanities and Innovation Studies, 2021)
Christianity and paganism are reciprocal; Christianity is necessary for revelation to be fulfilled, but the actual quality of this fulfillment depends upon the quality of the religious man transformed by revelation. Christianity, as a result of this, needs a natural religion, the same way it needs all human realities as the sole mission is to save what has first been created. The link between Gospel and culture is that Gospel whenever its introduced and established in a new culture, is “transposed” in a particular way a sweet melody into a new key. Moreover, the Gospel, when transposed from its biblical world to other cultural worlds, undergoes change itself as well as causing these other worlds to change. Crowther created an astonishing impact and contribution after his consecration in 1864; as he strived to indigenize or Africanize Christianity to make it possible for the Christian faith to be accepted by Africans without having to give up or disown their cultural values. This work seeks to find what part Henry Venn, the dynamic and accomplished secretary of the Church Missionary Society, played to see how Christian faith can go well together or combine with African beliefs and practices to produce Christianity which may become a religion for Africans. This work has shown that Henry Venn's ideas on native Church organization include: the native Church needs the ablest native pastors for its fuller development and that it should be under a native bishop and that a native Church is organized as a national institution. This work adopted a qualitative method that used historical and content analysis. This work concluded that for the Africanization of Christianity to be actualized, African Church must have its liturgy or incorporate what was good of the native religions to develop an authentically African Christianity.